MicroRNA-19a Targets Fibroblast Growth Factor-Inducible Molecule 14 and Prevents Tubular Damage in Septic AKI - Jun Hong; Bang-Chuan Hu; Liang Xu; Yang Zheng; Zi-Qiang Shao; Run Zhang; Xiang-Hong Yang; Ren-Hua Sun; Shi-Jing Mo (Analytical Cellular Pathology)
Fibroblast growth factor-inducible molecule 14 (Fn14) plays a principal role in triggering tubular damage during septic acute kidney injury (AKI). Here, we explore the mechanism underlying Fn14 deregulation in septic AKI. We identify Fn14 as a bona fide target of miR-19a, which directly binds to 3′ UTR of Fn14 for repression independent of cylindromatosis (CYLD), the deubiquitinase (DUB) downstream of miR-19a, and thereby antagonizes the LPS-induced tubular cell apoptosis. Genetic ablation of Fn14, but not of CYLD, abolishes the ability of miR-19a to antagonize the tubular apoptosis by lipopolysaccharide (LPS). In mice, systemic delivery of miR-19a confers protection against septic AKI. Our findings implicate that miR-19a may serve as a promising therapeutic candidate in the prevention of septic AKI.